2001
DOI: 10.4269/ajtmh.2001.64.1.11425158
|View full text |Cite
|
Sign up to set email alerts
|

Short report: differences in dihydrofolate reductase but not dihydropteroate synthase alleles in Plasmodium falciparum isolates from geographically distinct areas in Malaysia.

Abstract: Abstract. Dihydropteroate synthase (dhps) and dihydrofolate reductase (dhfr) alleles were typed in 67 Malaysian Plasmodium falciparum isolates. The isolates were collected from two geographically distinct locations: 51 from Sabah, Malaysian Borneo, where sulfadoxine/pyrimethamine (SDX/PYR) is used to treat uncomplicated malaria and 16 from Peninsular Malaysia where in vivo resistance to SDX/PYR has been reported. A total of seven dhps alleles were identified with no significant difference in allele frequency b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
6
16
0
Order By: Relevance
“…Three different alleles, namely ANRNL, ANRNI and AIRNI were detected (Table 2a). The most prevalent allele in this study is ANRNL (86.4%), which was absent in previous study conducted in Sabah about 15 years ago [4]. All isolates had mutation at position S108N and C59R accompanied by 86.4% (n = 19) mutation at I164L.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Three different alleles, namely ANRNL, ANRNI and AIRNI were detected (Table 2a). The most prevalent allele in this study is ANRNL (86.4%), which was absent in previous study conducted in Sabah about 15 years ago [4]. All isolates had mutation at position S108N and C59R accompanied by 86.4% (n = 19) mutation at I164L.…”
Section: Resultsmentioning
confidence: 55%
“…In vitro resistance of P. falciparum to PYR is primarily conferred by a non-synonymous point mutation at S108N and is progressively enhanced by mutations at residue N51I and/or C59R of pfdhfr . An additional mutation at I164L is associated with high-level clinical resistance to SDX/PYR [4,5]. In pfdhps , point mutations at A437G and K540E are considered responsible for SDX resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of dhfr mutations was weaker in group 2 patients than was that of pfcrt in group 1 patients. Although we found no significant associations between dhfr mutations and clinical response in group 2, we found that I164L, the mutation most predictive of clinical failure [14,15], was more prevalent in Binh Phuoc than Dac Lac, and there was a trend to its selection with treatment in Binh Phuoc. In addition, available isolates from group 2 patients (mostly from Binh Phuoc) with PCRconfirmed recrudescence had significantly higher pyrimethamine-sulfadoxine IC 50 values than did those isolates obtained from patients who were cured.…”
Section: Discussionmentioning
confidence: 70%
“…Reactions indicating the presence of both mutant and wild type alleles were reconfirmed under stringent digestion conditions. Similar methods were used to detect the dihydrofolate reductase (pfdhfr ) mutations N51I, C59R, S108N, and I164L [14][15][16]. The oligonucleotide primer pairs used for multilocus genotyping and for pfcrt and pfdhfr allelic typing did not amplify the P. vivax DNA that was included as a control in all assays.…”
Section: Study Sitesmentioning
confidence: 99%